How to effectively reverse life-thretening effects of non-vitamin K oral anticoagulants? - Łukasz Wołowiec; Joanna Banach; Daniel Rogowicz; Magdalena Węglarz; Walery Zukow; Władysław Sinkiewicz (Journal of Education, Health and Sport, 2017)
For several decades the vitamin K antagonist oral anticoagulants were the only outpatient therapy that existed to reduce the risk of stroke and thromboembolism until non-vitamin K oral anticoagulants (NOACs). Direct thrombin inhibitor: dabigatran and factor Xa inhibitors: apixaban, rivaroxaban, and edoxaban directly inhibit the coagulation cascade. DOACs have many advantages over warfarin. In general, the new agents have similar or lower bleeding risk than vitamin K antagonists, especially risk of intracranial bleeding. However, the biggest drawback of DOACs has been the lack of specific antidotes to reverse the anticoagulant effect in emergency situations.